The first Turcolana Argano & Pesce, 1980 (Isopoda: Cirolanidae) from the Greek mainland - Prevorčnik, Simona; Konec, Marjeta; Sket, Boris (Zootaxa, 2016)
Turcolana Argano & Pesce, 1980 is the isopod genus occurring in freshwater and brackish groundwater environments around the eastern Mediterranean. In this study, a revised diagnosis of the genus, an updated map of species distribution and a key to species are presented. The first cave dwelling species is described from the Melissotrypa Cave in central Greece, a highly troglomorphic Turcolana lepturoides sp. nov. Its principal distinguishing characters are elongated appendages: styliform uropods (twice as long as pleotelson), antennae (half as long as body) and pereopods (e.g. pereopod 7 45% as long as body). Mitochondrial DNA sequences (16S rRNA, 12S rRNA) of the new species are provided.